The effectiveness of STEM teaching in the development of the ability of middle school students to solve problems from the point of view of their teachers in The City of Onaizah - Al-Saeed, Mona Ibrahim (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the effectiveness of STEM teaching in developing the ability of middle school students to solve problems in the Qassim-Onaizah region, and to detect differences in the responses of the sample members about the effectiveness of stem curriculum in the development of the ability of middle school students to solve problems according to the changes in scientific qualification and years of experience, and to achieve the objectives of the study used the descriptive analytical method, and the questionnaire was the study tool applied to (50) middle school teachers in The City of Onaizah , and the results of the study indicated that the weight Relative to the effectiveness of stem curriculum in the development of the ability of middle school students to solve problems from the point of view of middle school teachers obtained a total average (3.82 out of 5) and equal to 76.34% i.e. with a degree of approval (large) on the paragraphs of the resolution, as the results revealed the absence of statistically significant differences between the responses of the individuals of the sample according to the changes of scientific qualification and years of experience, and based on the results the researcher made a number of recommendations, the most important of which The need to use stem curriculum to achieve the integration of science, mathematics, computer, and engineering materials, and the need to pay attention to the preparation of intensive training courses for teachers in the design and implementation of educational units in accordance with stem curriculum.
Keywords: STEM curriculum; the effectiveness of teaching; middle school students; problem solving; Onaizah